2022
DOI: 10.3138/canlivj-2021-0017
|View full text |Cite
|
Sign up to set email alerts
|

Late presentation of posterior reversible encephalopathy syndrome following liver transplantation in the setting of tacrolimus and cannabis use

Abstract: A 45-year-old female presented to hospital with confusion and visual disturbances. She had undergone a liver transplant 3 years prior for cirrhosis secondary to primary biliary cholangitis. Computed tomography and magnetic resonance imaging of the brain showed features consistent with posterior reversible encephalopathy syndrome. Her medications included tacrolimus, sirolimus, and prednisone. She reported smoking 4 grams of cannabis per day. Following cessation of tacrolimus, the patient’s encephalopathy and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The EVALI outbreak, though initially thought to be related to vaping nicotine, was ultimately found to be related to Vitamin E acetate which was added to counterfeit THC vaping products [36]. Data on the effects of cannabis in the pediatric transplant population are limited but studies suggest cannabis can inhibit tacrolimus metabolism and lead to increased concentrations [10,11].…”
Section: Cannabismentioning
confidence: 99%
See 1 more Smart Citation
“…The EVALI outbreak, though initially thought to be related to vaping nicotine, was ultimately found to be related to Vitamin E acetate which was added to counterfeit THC vaping products [36]. Data on the effects of cannabis in the pediatric transplant population are limited but studies suggest cannabis can inhibit tacrolimus metabolism and lead to increased concentrations [10,11].…”
Section: Cannabismentioning
confidence: 99%
“…Substance use is one factor that may worsen compliance which can lead to graft failure. In addition, substance use has the potential to directly affect the transplant graft via toxin-mediated damage [7,8] and interactions with immunosuppression regimens [9][10][11]. Thus, it is important that transplant teams are equipped to address substance use among adolescent patients in their clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, however, legalization and commercial production with implied quality control standards would make aspergillus infection less likely in this current era. Additionally, case reports found that cannabis interacts with immunosuppressants like tacrolimus by decreasing the metabolism of tacrolimus and increasing risks of toxicity (9,10). However, there is a lack of studies assessing the drug-drug interactions between cannabis and immunosuppressants in liver transplant recipients (11).…”
Section: Introductionmentioning
confidence: 99%